2016
DOI: 10.1002/anie.201511385
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Functionalized 4‐Aminoquinolines

Abstract: A diverse set of highly substituted 4-aminoquinolines was synthesized from ynamides, triflic anhydride, 2-chloropyridine, and readily accessible amides in a mild one-step procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 57 publications
0
26
0
Order By: Relevance
“…Although it is known that terminal sulfonyl ynamides are water sensitive, this was not a major concern during previous studies on metal-free systems, as the desired reactions outpaced any side-reactions. 34 However, during our copper catalyst screen, we found that the presence of the copper promoters facilitated the hydrolysis of the terminal sulfonyl ynamide 1a to its sulfonyl amide 2 (Scheme 1).…”
Section: -32mentioning
confidence: 98%
See 1 more Smart Citation
“…Although it is known that terminal sulfonyl ynamides are water sensitive, this was not a major concern during previous studies on metal-free systems, as the desired reactions outpaced any side-reactions. 34 However, during our copper catalyst screen, we found that the presence of the copper promoters facilitated the hydrolysis of the terminal sulfonyl ynamide 1a to its sulfonyl amide 2 (Scheme 1).…”
Section: -32mentioning
confidence: 98%
“…34 Alternative popular synthetic routes to ynamides include copper-catalysed amidative cross-coupling processes. [35][36][37][38][39][40][41][42][43] The sydnones could be accessed via a two-step procedure consisting of the nitrosation and cyclodehydration of Narylglycines, as extensively reported in the literature.…”
Section: -32mentioning
confidence: 99%
“…Recent further work on this family of transformations has led to the development of highly modular processes, allowing access to a wide range of heterocyclic structures. 42,43 While the aforementioned processes hinge on the addition of a two-carbon nucleophilic moiety, affording six-membered rings, Wang et al were able to elegantly utilise ethyl diazoacetate (EDA) as a one-carbon synthon (Scheme 14). 44 Forming substituted indole products (62), the authors exploited the inherent ambiphilic properties of EDA initially attacking the electrophilic nitrilium ion 60 and subsequently undergoing displacement of dinitrogen during cyclisation.…”
Section: Intermolecular Addition Of Carbon Nucleophilesmentioning
confidence: 99%
“…They obtained many 4-sulfonylamino quinolines (73) in good yield, which could then be easily converted to biologically useful amines by hydrolysis of the protecting group. Finally, Bräse and coworkers [45] described the synthesis of functionalized quinolines from sulfanyl ynamides 72 and electrophilically-activated aryl amides 71 under the influence of triflic anhydride and 2-chloropyridine ( Figure 32). Inspired by the work of Movassaghi, who developed this method to synthesize pyridine, pyrimidine, and β-carboline derivatives, the Bräse group applied this procedure to quinoline synthesis.…”
Section: Electrophilic Cyclizationmentioning
confidence: 99%